Análisis de las políticas de contratación laboral en el sector empresarial bananero del Ecuador. - Guillen Ordoñez, Raquel Alexandra; Mera Cumbicus, Gonzalo Rodolfo (My University, 2019)
The purpose of this research work is to analyze the labor procurement policies in force in Ecuador, with reference to the issuance of ministerial agreement No. MDT-2018-0074, which modifies the mode of recruitment banana sector, and implements the special work contract discontinued part-time, for the duration of the cycle generated by the special activity to be carried out in the sector, in this way, the State is satisfied and meets the circumstantial requirements of the Employer. Without considering that in Ecuador from 2015 on days the in definite contracting is being established as the typical modality of stable or permanent employment, and its duration or extinction will occur only by the causes and the procedures indicated in the Labor Code. Determining a legal impact, which causes labor instability to the worker who provides his lawful and personal services in the Ecuadorian banana sector, a conclusion that is based on the analysis of the recruitment policies applicable before and after of the issuance of Ministerial Agreement MDT-2018-0074, which was issued on 10 April 2018, and of interviews with banana workers.
El presente trabajo de investigación tiene como propósito analizar las políticas de contratación laboral vigentes en el Ecuador, tomando como referencia la expedición del Acuerdo Ministerial N° MDT-2018-0074, con el que se modifica la modalidad de contratación en el sector bananero, e implementa el contrato de trabajo especial discontinuo a jornada parcial, por el tiempo que dure el ciclo que genera la actividad especial a realizarse en el sector, de esta manera, el Estado se congracia y cumple con las exigencias circunstanciales del empleador. Sin considerar, que en el Ecuador a partir del año 2015 rige la contratación indefinida estableciéndose como la modalidad típica de contratación laboral estable o permanente, y su duración o extinción se producirá únicamente por las causas y los procedimientos señalados en el Código de Trabajo. Determinando una incidencia legal, que provoca una inestabilidad laboral al trabajador que presta sus servicios lícitos y personales en el sector bananero ecuatoriano, conclusión que se sustenta del análisis de las políticas de contratación aplicables antes y después de la expedición del Acuerdo Ministerial N° MDT-2018-0074, el cual fue emitido el 10 de abril del año 2018, y de las entrevistas que fueron realizadas a los trabajadores del sector bananero.
Keywords: ACUERDO MINISTERIAL; MDT-2018-0074; CONTRATO DE TRABAJO; ESTABILIDAD LABORAL